2019
DOI: 10.1590/1807-3107bor-2019.vol33.0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a resin-modified glass-ionomer with calcium on enamel demineralization inhibition: an in vitro study

Abstract: We assessed the effect of a new coating material based on resin-modified glass-ionomer with calcium (Ca) in inhibiting the demineralization of underlying and adjacent areas surrounding caries-like lesions in enamel. The measures used were surface hardness (SH) and cross-sectional hardness (CSH). Thirty-six bovine enamel specimens (3 × 6 × 2 mm) were randomly allocated into three groups (n = 12): No treatment (NT); resin-modified glass-ionomer with Ca (Clinpro XT Varnish, 3M ESPE) (CL), and fluoride varnish (Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(36 reference statements)
1
2
1
2
Order By: Relevance
“…Based on resin modified glass ionomer technology, fluoride release would be slower and extended (22) . The results from this study, regarding fluoride release of Clinpro XT, are consistent with the conclusion of Virupaxi, et al (8) , who stated that Clinpro XT had the highest fluoride mean release when compared to conventional fluoride varnishes, after evaluating the longevity of fluoride release from Clinpro XT, Flouritop SR and Flourprotector over a period of 6 months through salivary fluoride estimation, after 1 week, 1 month, 3 months and 6 months from varnishes application.The current study's findings, on the other hand, differ from those of Scotti et al (23) , who investigated the effect of Clinpro XT and Duraphat varnishes on inhibiting demineralization of underlying and adjacent areas surrounding carieslike lesions in enamel and measuring fluoride release. By the end of their study, they concluded that there was no statistically significant difference in the percentage of fluoride release among the three groups; this difference in conclusion could be attributed to the fact that they measured fluoride release in demineralized tooth structure, rather than sound tooth structure, as in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on resin modified glass ionomer technology, fluoride release would be slower and extended (22) . The results from this study, regarding fluoride release of Clinpro XT, are consistent with the conclusion of Virupaxi, et al (8) , who stated that Clinpro XT had the highest fluoride mean release when compared to conventional fluoride varnishes, after evaluating the longevity of fluoride release from Clinpro XT, Flouritop SR and Flourprotector over a period of 6 months through salivary fluoride estimation, after 1 week, 1 month, 3 months and 6 months from varnishes application.The current study's findings, on the other hand, differ from those of Scotti et al (23) , who investigated the effect of Clinpro XT and Duraphat varnishes on inhibiting demineralization of underlying and adjacent areas surrounding carieslike lesions in enamel and measuring fluoride release. By the end of their study, they concluded that there was no statistically significant difference in the percentage of fluoride release among the three groups; this difference in conclusion could be attributed to the fact that they measured fluoride release in demineralized tooth structure, rather than sound tooth structure, as in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…These results also are in agreement with Scotti et al (16) , they assessed that Clinpro XT showed better performance than fluoride. This fact could have occurred due to the chemical bond between glass ionomer of Clinpro XT Varnish and the tooth surface, which allows longer maintenance time.…”
Section: Discussionsupporting
confidence: 93%
“…It is considered to have advantages of longevity and sustainability, and it also provides good maneuverability with prolonged working times and short setting times achieved by light curing. It has been reported that the effectiveness of LCFV in the inhibition of enamel demineralization is comparable to conventional FV 8 . Moreover, recent clinical studies have shown that LCFV could effectively prevent enamel demineralization for a longer term compared with the conventional FV 9,10 .…”
Section: Introductionmentioning
confidence: 98%